Key processes and timescales of tropical earth formation - Sprafke, Tobias; Kadereit, Annette; Lauer, Felix; Rodrigues, Fernanda Costa G.; Sawakuchi, André Oliveira; Thiel, Christine; van Thuyne, John; Rodrigues, Leonor; Santos, Taís Almeida; Zipf, Lars; Szidat, Sönke; Tchomga, Philippe; et al. (Earth science reviews, 2024)
Understanding the formation of tropical yellow to red earth (TYRE) is essential for preserving soil multifunctionality in well-drained tropical landscapes. Weathering and bioturbation mutually interact in TYRE evolution, whereas allochthonous materials appear restricted to distinct (paleo)landscapes. A layered appearance of TYRE can result from quasi-constant deposition of invertebrate mound debris, outcompeting diffusional mixing. Age-depth profiles from optically stimulated luminescence (OSL) and charcoal radiocarbon (14Cchar) data of TYRE sites in different tropical landscapes, both from the literature and the present study, all reveal quasi-constant soil upbuilding, in accordance with our model. The rates of soil upbuilding are mostly in the range of 100-200 mm*ka−1, which conforms with published mounding rates of termites and ants. By comparison, geochemical transformation of rock to saprolite proceeds at rates at least one order of magnitude smaller. Termites mining saprolite, sometimes even below indurated subsoil, produce TYRE, thus linking the interconnected subsystems of differing process rates. The work of the bioengineers appears essential for transforming the deep-weathering products into well-structured TYRE. Future research may extend the provided database, the spatial scale, and the use of geochronology, coupled with paleoenvironmental proxies, in order to further enhance our understanding of tropical soil and landscape evolution, as one basis for advances in sustainable land use.
Online verfügbar: 10. Mai 2024, Artikelversion: 16. Mai 2024
Gesehen am 10.07.2025